2022
DOI: 10.3390/bios12020123
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of Metal Oxide Nanoparticles Modulates Neutrophil Extracellular Trap Formation

Abstract: Novel metal oxide nanoparticle (NP) contrast agents may offer safety and functionality advantages over conventional gadolinium-based contrast agents (GBCAs) for cancer diagnosis by magnetic resonance imaging. However, little is known about the behavior of metal oxide NPs, or of their effect, upon coming into contact with the innate immune system. As neutrophils are the body’s first line of defense, we sought to understand how manganese oxide and iron oxide NPs impact leukocyte functionality. Specifically, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 136 publications
(170 reference statements)
0
11
0
Order By: Relevance
“…In-house formulations of MnO and Mn 3 O 4 nanocrystals were systematically compared to commercially available MnO, Mn 2 O 3 , and Mn 3 O 4 nanocrystals purchased from two different companies (US Nano and Nanoshel) to evaluate their effectiveness as MRI contrast agents. As previously described, our In-house MnO and Mn 3 O 4 formulations were synthesized via thermal decomposition of Mn­(II)­AcAc with oleylamine as the capping agent. ,, Bare nanocrystals were characterized for crystal structure, chemical composition, impurities, size, morphology, and coating. Hydrophobic bare nanocrystals were encapsulated within PLGA and characterized for surface chemistry, size, morphology, encapsulation efficiency, pH-sensitive release of manganese ions, and resulting MRI signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-house formulations of MnO and Mn 3 O 4 nanocrystals were systematically compared to commercially available MnO, Mn 2 O 3 , and Mn 3 O 4 nanocrystals purchased from two different companies (US Nano and Nanoshel) to evaluate their effectiveness as MRI contrast agents. As previously described, our In-house MnO and Mn 3 O 4 formulations were synthesized via thermal decomposition of Mn­(II)­AcAc with oleylamine as the capping agent. ,, Bare nanocrystals were characterized for crystal structure, chemical composition, impurities, size, morphology, and coating. Hydrophobic bare nanocrystals were encapsulated within PLGA and characterized for surface chemistry, size, morphology, encapsulation efficiency, pH-sensitive release of manganese ions, and resulting MRI signal.…”
Section: Resultsmentioning
confidence: 99%
“…In-house and commercialized MnO, Mn 2 O 3 , and Mn 3 O 4 nanocrystals were encapsulated in PLGA using an oil-in-water emulsion solvent evaporation method as previously described. , Each nanocrystal typeIn-house MnO and Mn 3 O 4 ; US Nano’s Mn 2 O 3 and Mn 3 O 4 ; and Nanoshel’s MnO, Mn 2 O 3 -30 nm, Mn 2 O 3 -80 nm, and Mn 3 O 4 was encapsulated within PLGA in triplicate. For each replicate, approximately 100 mg of PLGA was dissolved in 2 mL of dichloromethane (DCM).…”
Section: Methodsmentioning
confidence: 99%
“…Several papers have reported nanoparticle-induced NETosis, which may aggravate the thrombogenic nature of the SARS-CoV-2 infection. Thus far, nanoparticle-induced NETosis has been reported for nanoparticles based on silver 38 , gold 39,40 , iron oxide 41,42 , manganese oxide 41 , graphene oxide 43 , cationic lipids 44 , polystyrene 45 and nanodiamonds 45 , although further research may reveal other materials exhibiting similar behaviour. There is as-of-yet contention over whether this is caused by the nanoparticles themselves or their dissolution products 46 .…”
Section: Activation Pathways Of Sars-cov-2-induced Netosis and Subseq...mentioning
confidence: 99%
“…Surface functionalization with biocompatible layers of human serum albumin or dextran has also been shown to reduce the NET-generating properties of iron oxide nanoparticles 42 , providing another strategy for minimizing NETosis. Interestingly, several papers have indicated that the addition of polyethylene glycol-which is normally seen as highly biocompatible-does not reduce NETosis 40 , and may even aggravate it 41 . Due to these variabilities, it is suggested that nanomedicines designed to treat COVID-19-induced thrombosis are optimized and tested pre-clinically for their ability to generate NETosis, to avoid potential pro-thrombotic effects.…”
Section: Activation Pathways Of Sars-cov-2-induced Netosis and Subseq...mentioning
confidence: 99%
“…However, in most cases, the magnetic core should be completely protected by various organic and inorganic materials. One of the popular approaches to achieve this is polymer coating [13,[49][50][51][52][53][54]. A wide range of polymers and their functional groups provide excellent diversification of colloidal stability, charge, solubility in water, salt and temperature stability, viscosity, and further modification by address or reporter groups [13,[49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%